The Effect of Obesity on the Severity of COVID-19: A Meta-Analysis - Okky Nurlita Sari; Bhisma Murti; Ignatius Loyola Sukamto (Journal of Epidemiology and Public Health, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which first appeared at the end of 2019 in the city of Wuhan, China. Obesity is one of the comorbidities that increases the risk of COVID-19 severity. This study aims to estimate the magnitude of the effect of obesity on the risk of COVID-19 severity based on similar previous primary studies.Subjects and Method: This research is a systematic review and meta-analysis conducted by following the PRISMA flow diagram. The process of searching for articles through Google Scholar, PubMed and ScienceDirect journal databases by selecting articles published from 2020 to 2021. The keywords used include: